Microneurosurgical Management of Upper Cervical Spinal Schwannoma: An Experience of 30 Cases (Bangladesh Journal of Neurosurgery, 2019)
Aim: We prospectively recorded the clinical features, radiological features, surgical approaches & findings, postoperative follow up & ultimate neurological outcome of upper cervical spinal schwannomas and then we evaluated the records retrospectively. Materials and Method: 30 upper cervical spinal schwannomas patient who underwent surgery (microneurosurgically) from 2007 to 2014 in the department of neurosurgery Dhaka Medical College and private hospitals are included in this retrospective study. After operation all patients were followed up regularly both clinically and neuro-radiologically.Results: Out of 30 cases 16 male and 14 females. The male to female ratio was 1.4: 1, Age range from 8 to 60 years with mean age 35 Years. Most of the patients are in middle years age group The mean duration of symptoms at the time of presentation was 32 months (range 06 months-5 years). Four schwannomas were completely extradural, fourteen were intradural and rest twelve were intradural or hourglass type (both extra and intradural) as identified during surgery. The posterior midline approach was used in all patients. A C2 hemilaminectomy or C2 laminectomy with or without cutting of posterior arch of atlas was used for most intradural and large in terdural C2 schwannomas. Tumor removal was complete in all cases. Preservation of the nerve root fibers was not possible in 18 cases and was possible only in 12 cases. In one patients CSF leak developed after operation. One patient who had severe myelopathic features with bed sore failed to improve and expired 5 months after operation. Rest of the patients showed postoperative improvement in their preoperative symptoms and returned to their normal life by the end of sixth month. There was one tumor recurrence in any patient till last follow up.Conclusion: Proper 3-D anatomical orientation & physiological knowledge, deep neuro-radiological observation, pathological appreciations and micro-neurosurgical skill and expertization can make the surgical management of these tumors ( in a surgically complex site) simple with gratifying result (i.e.neurological outcome) without extensive bone removal or soft tissue manipulation through a standard midline posterior approach.Bang. J Neurosurgery 2019; 9(1): 44-48